Implementasi System Informasi: Dari Resistensi, Rekayasa Bisnis, hingga Penciptaan Kemakmuran - Yazid Yazid (Jurnal Siasat Bisnis, 2001)
It is hoped that by using information system (IS) or information technology (IT) business world will be able to take more and more benefits, and customers could be more satisfied. IT is not surprising, therefore, if the decision on information system investment becomes an integral part of the overall organization’s strategies. Yet, the success of IS development much depends on several factors such as the ability of management to identify the sources of and overcome change resistance. Satisfying customers is very promising effort: increase cash flow and profit. Yet, the result, mainly, depends on the management or researchers’ perception about satisfaction score, the costs should be incurred, and the management understanding about the concept and tools of IS. This paper will discuss about change resistance and alternative ways to overcome the problem, satisfaction trap, the important of cost reduction in IS implementation, and concept and tool to be understood by managers, especially the managers of service organizations.Keywords :    change resistence, information system, customer satisfaction